Local buckling of FRP thin-walled plates, shells and hollow sections with curved edges and arbitrary lamination. (November 2021) - Higginson, K.; Fernando, D.; Veidt, M.; Burnton, P.; You, Z.; Heitzmann, M.
Abstract: Extensive studies have been undertaken on the local buckling of FRP members. However, the scope of the existing research largely remains limited to those with rectangular faces. As the geometry of the member faces can affect the local buckling capacity, thin-walled members can possess higher buckling loads for a given volume of material when properly shaped. As such, consideration of non-rectangular faces is necessary, not only to cater for applications where non-rectangular profiles are commonly used, but also to exploit the potential for optimization of buckling capacity capable by using nonstandard cross-sections. In addition, the fibre layup of the lamella, and therefore the resulting mechanical properties of the face laminates, also influences the buckling capacity of the structural member. Hence, the optimal section geometry should also consider the fibre layups of the laminate. This paper presents a semi-analytical solution for the local buckling capacity of thin-walled members with faces of arbitrary geometry and material stacking sequence. The methodology adopts a Rayleigh–Ritz energy approach in combination with a Discrete Plate Analysis. Verifications have shown that the solution is capable to predict the local buckling capacity of the sections with acceptable levels of accuracy. Highlights: Local buckling often governs the failure of thin walled FRP composite members. Introducing curved edges can increase the buckling capacity of FRP composite members. Rayleigh Ritz method can solve the local buckling capacity of curved edge plates. Discrete plate analysis is used for calculating the buckling capacity of members. Geometry and stacking sequence are tailored for the optimization of FRP members.